Effect of the Molecular Structure of Poly(3-hydroxybutyrate- co-3-hydroxyvalerate) (P(3HB-3HV)) Produced from Mixed Bacterial Cultures on Its Crystallization and Mechanical Properties - Bossu, Julie (2021)
grant agreement no. 773375